Improvement of the regulatory framework for the regulation of non-profit organizations and social entrepreneurship in Kazakhstan - Pritvorova, T.P.; Spanova , B.K. (BUKETOV BUSINESS REVIEW, 2019)
In the article the issues of improving the regulatory framework for the regulation of non-profit organizations and social entrepreneurship in Kazakhstan are considered. In Kazakhstan the issues of the regulatory framework for social entrepreneurship are just beginning to be discussed and considered in the context of the characteristics of the non-profit sector. It is analyzed that in Kazakhstan there is no any form of legal regulation and legal definition of social entrepreneurship, and the question of creating a separate law on social entrepreneurship is debatable, since in many countries there is no practice of applying a specific legal form of registration as a special type of cooperative or company, but there is a legal qualification of the state of the organization. It is determined that in the reform of the legislation it is necessary to proceed from the European concept of social economy, which does not draw a strict border between the market and public spending and believes that non-profit organizations and social entrepreneurs work for the social economy. Therefore, the mixing in the organization of the state social order and income earned in the open market is quite compatible, if the mission of the organization is maintained. The authors found that non-profit organizations in Kazakhstan can operate in several organizational and legal forms and within the regulated list of activities covering all areas of the public sector. For non-profit organizations, it is proposed to provide the deductions from taxable income in the Tax code, to introduce an obligation for non-profit organizations to provide a mechanism for collective management.